Spherical halloysite mesoporous composite material and preparation method thereof as well as catalyst for preparing isobutene by dehydrogenation of isobutane and application of catalyst
By using spherical esolite mesoporous composite materials as support, the poor dispersion of active metal components caused by the small specific surface area of the carrier in the prior art is solved, and the high conversion and selectivity of isobutane dehydrogenation reaction is achieved, and the problem of easy carbon deposition of the carrier is avoided.
Patent Information
- Application Number
- CN202311378942.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the support specific surface area of isobutane dehydrogenation to isobutene catalyst is small, resulting in poor dispersion of active metal components on the support surface, affecting the diffusion of raw materials and products during the reaction.
The spherical mesoporous composite material of erylosite is used as a carrier, and the specific preparation method, including the combination of template agents, solvents and acid aqueous solutions, is used to crystallize, suction filtration, ball milling and spray drying, and the erylosite mesoporous composite material with excellent mesoporous structure is prepared.
The active metal components are well dispersed on the support surface, which improves the conversion rate of isobutane dehydrogenation reaction and the selectivity of isobutene, and avoids the problem of carbon deposition and inactivation of activated alumina support.
Smart Images

Figure CN119869507A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of low-carbon alkane dehydrogenation catalysts, and in particular to a spherical eidolite mesoporous composite material and a preparation method thereof, and an isobutane dehydrogenation catalyst for producing isobutene and an application thereof. Background Art
[0002] With the continuous innovation of material preparation methods and processes, clay composites have been successfully used in biomedicine, automobiles, petroleum, and wastewater treatment.
[0003] When designing and synthesizing clay composites, it is necessary to consider not only the chemical composition of the clay, but also factors such as the particle size, morphology and surface charge of the clay. Halloysite nanotubes (HNTs) are tubular aluminosilicate clays with large specific surface area, nanotube structure and good biocompatibility; at the same time, due to the different chemical composition of the inner and outer surfaces of HNTs (the outer surface is composed of Si-O, and the surface of the inner cavity is composed of Al-OH) and charge properties (the inner surface is positively charged and the outer surface is negatively charged), after modification, they can be used in the preparation of hydrophobic coatings, oil-water separation, catalysis, drug release and other fields.
[0004] In order to improve the reaction performance of isobutane dehydrogenation to isobutene catalysts, researchers have done a lot of work, such as improving catalyst performance by changing the catalyst preparation method (Industrial Catalysis, 2014, 22(2):148-153), improving catalyst stability by adding additives (Catal. Today, 2000, 55(3):213-223), and improving the catalyst's ability to resist carbon deposition by improving the carrier performance (Journal of Fuel Chemistry and Technology, 2013, 41(12):1481-1487).
[0005] However, the currently commonly used carriers have a small specific surface area, which is not conducive to the dispersion of active metal components on the carrier surface, nor is it conducive to the diffusion of raw materials and products during the reaction. Therefore, the selection of an excellent carrier is an urgent problem to be solved in the field of isobutane dehydrogenation to isobutylene. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem that the carrier commonly used in the prior art for preparing isobutene by dehydrogenating isobutane has a small specific surface area, which is not conducive to the dispersion of active metal components on the carrier surface and the diffusion of raw materials and products in the reaction process. A spherical izolite mesoporous composite material and a preparation method thereof, an isobutane dehydrogenation to isobutene catalyst and an application thereof are provided. The present invention adopts a novel izolite mesoporous composite material, which is conducive to good dispersion of active metal components on the carrier surface. When the active metal component loading amount is low, it can be ensured that the prepared isobutane dehydrogenation to isobutene catalyst has excellent dehydrogenation performance, and the isobutane conversion rate and isobutene selectivity are improved.
[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a spherical olite mesoporous composite material, wherein the preparation method comprises:
[0008] (1) in the presence of a template, trimethylpentane and ethanol, tetramethoxysilane is brought into contact with an acidic aqueous solution for the first time to obtain a mixture, and the mixture is subjected to crystallization, suction filtration and washing to obtain a mesoporous silica filter cake;
[0009] (2) contacting the water glass with the inorganic acid for a second time, and filtering and washing the mixture obtained after the second contact to obtain a silica gel filter cake;
[0010] (3) ball-milling the mesoporous silica filter cake, the silica gel filter cake and the elutingite together to obtain a solid powder;
[0011] (4) preparing the solid powder into a slurry in the presence of deionized water and then spray drying the slurry;
[0012] (5) calcining the product obtained in step (4) to remove the template, thereby obtaining a spherical izolite mesoporous composite material.
[0013] The second aspect of the present invention provides a spherical iodite mesoporous composite material prepared by the above-mentioned preparation method.
[0014] The third aspect of the present invention provides a catalyst for the dehydrogenation of isobutane to produce isobutene, wherein the catalyst for the dehydrogenation of isobutane to produce isobutene comprises a carrier and an active metal component loaded on the carrier, wherein the carrier is the spherical eidolite mesoporous composite material described above.
[0015] A fourth aspect of the present invention provides an application of the aforementioned isobutane dehydrogenation to isobutene catalyst in an isobutane dehydrogenation reaction;
[0016] Preferably, the conditions for the isobutane dehydrogenation reaction include: a reaction temperature of 530-630°C, a reaction pressure of 0.05-0.3 MPa, a molar ratio of isobutane to hydrogen in the raw material of 1:(0.2-5), and an isobutane mass space velocity of 1 h -1 -10h -1 .
[0017] Through the above technical scheme, the catalyst for isobutane dehydrogenation to isobutene prepared by the method provided by the present invention has the following advantages:
[0018] (1) The isobutane dehydrogenation catalyst to isobutene prepared by the method of the present invention does not use activated alumina as a carrier, thus overcoming the problem that the catalyst surface prepared by the current activated alumina carrier is prone to carbon deposition, which leads to rapid deactivation;
[0019] (2) The present invention adopts a novel eidolite mesoporous composite material, which is conducive to the good dispersion of active metal components on the carrier surface. When the active metal component loading is low, it can ensure that the prepared isobutane dehydrogenation to isobutylene catalyst has excellent dehydrogenation performance, thereby improving the isobutane conversion rate and isobutylene selectivity.
[0020] (3) The present invention can adopt a co-impregnation method to replace the conventional step-by-step impregnation method, without affecting the catalyst performance. The preparation process is simple, the conditions are easy to control, and the product reproducibility is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention. In the accompanying drawings:
[0022] Figure 1 is the X-ray diffraction pattern of the novel iodite mesoporous composite material prepared in Example 1 of the present invention;
[0023] Figure 2 This is a scanning electron microscope image of the novel iodine mesoporous composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] As mentioned above, the first aspect of the present invention provides a method for preparing a spherical olite mesoporous composite material, wherein the preparation method comprises:
[0026] (1) in the presence of a template, trimethylpentane and ethanol, tetramethoxysilane is brought into contact with an acidic aqueous solution for the first time to obtain a mixture, and the mixture is subjected to crystallization, suction filtration and washing to obtain a mesoporous silica filter cake;
[0027] (2) contacting the water glass with the inorganic acid for a second time, and filtering and washing the mixture obtained after the second contact to obtain a silica gel filter cake;
[0028] (3) ball-milling the mesoporous silica filter cake, the silica gel filter cake and the elutingite together to obtain a solid powder;
[0029] (4) preparing the solid powder into a slurry in the presence of deionized water and then spray drying the slurry;
[0030] (5) calcining the product obtained in step (4) to remove the template, thereby obtaining a spherical izolite mesoporous composite material.
[0031] According to the present invention, in step (1), the template is a triblock copolymer of polyethylene oxide-polyoxyisobutylene-polyoxyethylene.
[0032] According to the present invention, the acidic aqueous solution is a buffer solution of acetic acid and sodium acetate, and the pH value of the buffer solution is 1-6.
[0033] According to the present invention, the temperature of the first contact is 10-60° C., and the contact time is 10-72 hours.
[0034] According to the present invention, the crystallization temperature is 30-150° C., and the crystallization time is 10-72 hours.
[0035] According to the present invention, the suction filtration separation is a method of separating liquid and solid particles well known to those skilled in the art, which utilizes air pressure to separate liquid and solid particles or a mixture of liquid and liquid.
[0036] According to the present invention, the washing conditions are not particularly limited. For example, the washing process may include: obtaining a solid product after filtration, repeatedly washing the solid product with distilled water (the number of washing times may be 2-10) and then filtering.
[0037] According to the present invention, in step (2), the pH value of the solution of water glass and the inorganic acid is 2-4;
[0038] According to the present invention, the temperature of the second contact is 10-60° C., and the contact time is 1-5 hours.
[0039] According to the present invention, in step (2), the molar ratio of the template: the ethanol: the acidic aqueous solution: the trimethylpentane: the tetramethoxysilane is 1: (100-500): (150-900): (200-500): (50-200).
[0040] According to the present invention, the weight ratio of the water glass to the inorganic acid is (3-6):1.
[0041] According to the present invention, the weight ratio of the mesoporous silica filter cake, the silica gel filter cake and the elosite is (1-10): (1-10): (1-10).
[0042] According to the present invention, in step (3), the ball milling treatment is preferably carried out in the presence of a protective gas (for example, one or more of nitrogen, argon or helium, preferably nitrogen).
[0043] According to the present invention, the ball milling process can be carried out in a ball mill, wherein the number of grinding balls in the ball mill can be reasonably selected according to the size of the ball milling jar equipped in the ball mill, for example, for a ball milling jar of 50-150 mL in size, 20-80 grinding balls can usually be used.
[0044] According to the present invention, the material of the grinding balls can be agate or polytetrafluoroethylene, preferably agate.
[0045] According to the present invention, the ball milling treatment can break large particles in the elosite mesoporous composite material and agglomerate small particles, further improving the pore connectivity of the elosite mesoporous composite material, thereby providing more binding sites for the active metal components, improving the dispersibility of the active metal components, and enhancing the geometric effect and electronic effect between the active metal components loaded thereon and the carrier, thereby further improving the catalytic effect of the active metal components on the dehydrogenation of isobutane, while also improving the conversion rate of isobutane and the selectivity of isobutylene.
[0046] According to the present invention, preferably, the ball milling treatment is carried out under conditions such that the average particle diameter of the modified olivine mesoporous composite material obtained by ball milling is 0.5-15 μm.
[0047] According to the present invention, in step (4), the weight ratio of the solid powder to the deionized water is (10-28):30.
[0048] According to the present invention, the water-locking spray drying is carried out under the condition of nitrogen protection throughout the process. In addition, the spray drying adopts a spray dryer with model LPG100 purchased from Wuxi, Jiangsu.
[0049] According to the present invention, in step (5), the conditions for calcination treatment to remove the template include: temperature of 500-550° C. and time of 8-9 hours.
[0050] According to the present invention, the specific surface area, pore volume and average pore size of the eidolite mesoporous composite material can be further increased by the ball milling and calcination treatment of the present invention, but the 2D hexagonal pore structure of the mesoporous material will not be changed.
[0051] The second aspect of the present invention provides a spherical iodite mesoporous composite material prepared by the above-mentioned preparation method.
[0052] According to the present invention, the average particle diameter of the spherical enamel mesoporous composite material is 20-60 microns, the specific surface area is 50-600 square meters / gram, the pore volume is 0.5-1.5 milliliters / gram, and the most probable pore diameters are 2-15 and 10-40 nanometers; preferably, the average particle diameter of the spherical enamel mesoporous composite material is 20-60 microns, the specific surface area is 50-300 square meters / gram, the pore volume is 1-1.5 milliliters / gram, and the most probable pore diameters are 2-9 and 20-25 nanometers.
[0053] In the present invention, when the structural parameters of the olivine mesoporous composite material are preferably controlled within the above range, it can be further ensured that the modified olivine mesoporous composite material is not easy to agglomerate, thereby ensuring the catalytic effect in the process of isobutane dehydrogenation to isobutylene.
[0054] The third aspect of the present invention provides a catalyst for the dehydrogenation of isobutane to produce isobutene, wherein the catalyst for the dehydrogenation of isobutane to produce isobutene comprises a carrier and an active metal component loaded on the carrier, wherein the carrier is the spherical eidolite mesoporous composite material described above.
[0055] According to the present invention, the active metal component is selected from one or more of platinum, tin, zinc, magnesium, calcium and gallium; preferably one or more of platinum, tin and zinc; more preferably contains platinum and tin and / or zinc; in the present invention, the precursor of platinum can be H2PtCl6, the precursor of tin can be SnCl4·5H2O and the precursor of zinc can be ZnCl2.
[0056] According to the present invention, the spherical eidolite mesoporous composite material prepared by the method of the present invention can reduce the amount of active metal components when preparing a catalyst for dehydrogenating isobutane to isobutylene. Therefore, when the active metal component is a precious metal, the method of the present invention can save costs.
[0057] According to the present invention, based on the total weight of the isobutane dehydrogenation to isobutylene catalyst, the content of the modified olite mesoporous composite material is 98-99% by weight, the content of the active component Pt in terms of Pt element is 0.2-0.5% by weight, and the content of other active metal components other than Pt in terms of metal elements is 0.8-1.5% by weight; preferably, based on the total weight of the isobutane dehydrogenation to isobutylene catalyst, the content of the olite mesoporous composite material is 98.0-99.0% by weight, the content of the main active component Pt in terms of Pt element is 0.2-0.5% by weight, the content of Sn in terms of Sn element is 0.4-0.7% by weight, and the content of Zn in terms of Zn element is 0.4-0.8% by weight. This is conducive to maximizing the synergistic effect between each component and the carrier to obtain the best catalytic activity.
[0058] According to the present invention, when the active metal component is loaded on the carrier, an impregnation method can be used. During the impregnation process, the active metal ions in the impregnation solution can enter the pores of the elosite mesoporous composite material by relying on the capillary pressure of the pores of the elosite mesoporous composite material. At the same time, the active metal ions will also be adsorbed on the surface of the elosite mesoporous composite material until adsorption equilibrium is reached.
[0059] In the present invention, the impregnation method is not particularly limited. When the active metal components are at least two, the traditional step-by-step impregnation method can be adopted. However, the inventors of the present invention have found that the method of the present invention can adopt a co-impregnation method to achieve the same effect, that is, the method of the present invention also saves the impregnation step.
[0060] In the present invention, preferably, the impregnation conditions include: mixing and contacting the modified eigensite mesoporous composite material with a solution containing an active metal component precursor, the impregnation temperature may be 20-100° C., and the impregnation time may be 2-20 h.
[0061] According to the present invention, the preparation process of the isobutane dehydrogenation to isobutene catalyst further includes removing the solvent, drying and calcining after impregnation.
[0062] According to the present invention, the process of removing the solvent can adopt conventional methods in the art, for example, a rotary evaporator can be used to remove the solvent in the system.
[0063] According to the present invention, the drying may be performed in a drying oven, and the drying conditions may include: a temperature of 70-150° C. and a time of 3-16 hours.
[0064] According to the present invention, the calcination may be carried out in a muffle furnace, and the calcination conditions may include: a temperature of 500-650° C. and a time of 3-12 hours.
[0065] A fourth aspect of the present invention provides an application of the aforementioned isobutane dehydrogenation to isobutene catalyst in an isobutane dehydrogenation reaction.
[0066] According to the present invention, the isobutane dehydrogenation can be carried out according to conventional methods in the art. For example, the isobutane dehydrogenation reaction method comprises: subjecting isobutane to a dehydrogenation reaction in the presence of a catalyst and hydrogen.
[0067] According to the present invention, the conditions for the isobutane dehydrogenation reaction include: a reaction temperature of 530-630°C, a reaction pressure of 0.05-0.3 MPa, a molar ratio of isobutane to hydrogen in the raw material of 1:0.2-5, and an isobutane mass space velocity of 1h -1 -10h -1 .
[0068] When the isobutane dehydrogenation catalyst for preparing isobutene prepared by the method provided by the present invention is used to catalyze the isobutane dehydrogenation reaction, the conversion rate of isobutane and the selectivity of isobutene can be greatly improved.
[0069] The present invention will be described in detail below through examples.
[0070] In the following examples and comparative examples:
[0071] X-ray diffraction analysis was performed on an X-ray diffractometer model D8 Advance purchased from Bruker AXS, Germany;
[0072] The pore structure parameter analysis was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, USA;
[0073] The specific surface area, pore volume and average pore size of the samples were calculated using the BET method;
[0074] The rotary evaporator was manufactured by IKA, Germany, model RV10 digital;
[0075] The active metal component content of the isobutane dehydrogenation catalyst to isobutene was measured on a wavelength dispersive X-ray fluorescence spectrometer of model Axios-Advanced purchased from PANalytical of the Netherlands;
[0076] The analysis of the reaction product components was carried out on a gas chromatograph model 7890A purchased from Agilent;
[0077] The template agent triblock copolymer polyethylene glycol-polypropylene glycol-polyethylene glycol was purchased from Aldrich Company with analytical purity; other reagents were purchased from Sinopharm Chemical Reagent Co., Ltd. with analytical purity.
[0078] In the following experimental examples and comparative examples:
[0079] Conversion rate of isobutane (%) = amount of isobutane consumed in the reaction / initial amount of isobutane × 100%;
[0080] Isobutene selectivity (%) = amount of isobutane consumed to produce isobutene / total isobutane consumption × 100%.
[0081] Example 1
[0082] This example is used to illustrate the preparation of the olite mesoporous composite material, the preparation method of the isobutane dehydrogenation catalyst to prepare isobutane, and its application in the isobutane dehydrogenation reaction.
[0083] (1) Preparation of mesoporous composite materials of enamel
[0084] Preparation of Iolite Mesoporous Composite Material Carrier:
[0085] 1.0 g of triblock copolymer polyethylene glycol-polypropylene glycol-polyethylene glycol (Aldrich, P123) and 1.69 g of ethanol were added to 28 ml of acetic acid and sodium acetate buffer solution (pH = 4.4), and stirred at 15°C until the polyethylene glycol-polypropylene glycol-polyethylene glycol was completely dissolved, then 6 g of trimethylpentane was added to the above solution, and stirred at 15°C for 8 hours, and then 2.13 g of tetramethoxysilane was added to the above solution, and stirred at 15°C for 20 hours, and then the solution was transferred to a polytetrafluoroethylene-lined reactor, and after oven crystallization at 60°C for 24 hours, it was filtered and washed with distilled water to obtain a mesoporous material filter cake;
[0086] A 15 wt % water glass and a 12 wt % sulfuric acid solution were reacted for 1.5 hours at a water glass: sulfuric acid weight ratio of 5:1, the pH was adjusted to 3 with 98 wt % sulfuric acid, and the reaction material was filtered and washed with distilled water until the sodium ion content was 0.02 wt %, to obtain a silica gel filter cake.
[0087] Put 10g of the prepared mesoporous silica filter cake, 10g of silica gel filter cake and 10g of enamel powder into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3mm, the number is 1, and the rotation speed is 400r / min. Close the ball mill, and mill for 1 hour at a temperature of 60°C in the ball mill to obtain 28g of solid powder; dissolve the solid powder in 30g of deionized water, spray dry at 200°C and a rotation speed of 12000r / min; calcine the product obtained after spray drying at 500°C in a muffle furnace for 8 hours to remove the template agent, and obtain 25g of the target product, one-dimensional pore double pore distribution enamel mesoporous composite material A1 carrier without template agent.
[0088] XRD and ASAP2020-M+C adsorption instrument were used to characterize the mesoporous composite material A1 of elosite. The specific surface area of the mesoporous composite material A1 of elosite is 300m 2 / g, the pore volume is 1.5ml / g, and the average pore diameter is 9nm and 25nm.
[0089] Figure 1 This is the X-ray diffraction spectrum of the glazeite mesoporous composite material prepared in Example 1, with the abscissa being 2θ(°) and the ordinate being intensity. It can be clearly seen from the XRD spectrum that the mesoporous molecular sieve material A1 has a diffraction peak in the small angle region, indicating that the glazeite mesoporous composite material A1 has a 2D hexagonal pore structure unique to mesoporous materials.
[0090] Figure 2 This is a SEM image of the microscopic morphology of the spherical glazeite mesoporous composite material A1 prepared in Example 1. As can be seen from the image, the microscopic morphology of the spherical glazeite mesoporous composite material A1 is microspheres with a particle size of 20-30 μm, and its dispersion performance is good.
[0091] (2) Preparation of catalyst for dehydrogenation of isobutane to isobutene
[0092] 0.080 g H2PtCl6·6H2O, 0.177 g SnCl4·5H2O and 0.147 g ZnCl2 were dissolved in 100 mL deionized water in a round-bottom flask to obtain a mixed solution; 10 g of the modified iodite mesoporous composite material A1 prepared above was added to the mixed solution for co-impregnation treatment, and after continuous stirring and reaction for 8 hours in a water bath at 50°C, the solvent water in the system was evaporated by a rotary evaporator to obtain a solid product; the solid product was placed in a drying oven at a temperature of 110°C and dried for 6 hours. Then, the catalyst was calcined in a muffle furnace at 550° C. for 8 h to obtain an isobutane dehydrogenation to isobutene catalyst Cat-1. In the isobutane dehydrogenation to isobutene catalyst Cat-1, based on the total weight of the isobutane dehydrogenation to isobutene catalyst Cat-1, the content of the platinum component calculated as platinum element is 0.3 weight%, the content of the tin component calculated as tin element is 0.6 weight%, the content of the zinc component calculated as zinc element is 0.7 weight%, and the rest is a carrier.
[0093] Example 2
[0094] This example is used to illustrate the preparation of the olite mesoporous composite material, the preparation method of the isobutane dehydrogenation catalyst to prepare isobutane, and its application in the isobutane dehydrogenation reaction.
[0095] (1) Preparation of mesoporous composite materials of enamel
[0096] 1.0 g of triblock copolymer polyethylene glycol-polypropylene glycol-polyethylene glycol (Aldrich, P123) and 1.69 g of ethanol were added to 28 ml of acetic acid and sodium acetate buffer solution (pH = 4.4), and stirred at 15°C until the polyethylene glycol-polypropylene glycol-polyethylene glycol was completely dissolved, then 6 g of trimethylpentane was added to the above solution, and stirred at 15°C for 8 hours, and then 2.13 g of tetramethoxysilane was added to the above solution, and stirred at 15°C for 20 hours, and then the solution was transferred to a polytetrafluoroethylene-lined reactor, and after oven crystallization at 60°C for 24 hours, it was filtered and washed with distilled water to obtain a mesoporous material filter cake;
[0097] A 15 wt % water glass and a 12 wt % sulfuric acid solution were reacted for 1.5 hours at a water glass: sulfuric acid weight ratio of 5:1, the pH was adjusted to 3 with 98 wt % sulfuric acid, and the reaction material was filtered and washed with distilled water until the sodium ion content was 0.02 wt %, to obtain a silica gel filter cake.
[0098] Put 10 grams of mesoporous silica filter cake, 10 grams of silica gel filter cake and 1 gram of enamel powder prepared above into a 100 ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3 mm, the number is 1, and the rotation speed is 400 r / min. Close the ball mill, and mill at a temperature of 60°C in the ball mill for 1 hour to obtain 18 grams of solid powder; dissolve the solid powder in 30 grams of deionized water, spray dry at 200°C and a rotation speed of 12000 r / min; calcine the product obtained after spray drying at 500°C in a muffle furnace for 8 hours to remove the template agent, and obtain 15 grams of the target product of one-dimensional pore double pore distribution enamel mesoporous composite material carrier A2 without template agent.
[0099] The specific surface area of the mesoporous composite material A2 is 200 m 2 / g, the pore volume is 1.0ml / g, and the average pore diameter is 2nm and 25nm.
[0100] (2) Preparation of catalyst for dehydrogenation of isobutane to isobutene
[0101] 0.107g H2PtCl6·6H2O and 0.354g SnCl4·5H2O were dissolved in 100mL deionized water in a round-bottom flask to obtain a mixed solution; 10g of the modified olite mesoporous composite material A2 prepared above was added to the mixed solution for co-impregnation treatment, and the reaction was continuously stirred for 14 hours in a water bath at 30°C, and the solvent water in the system was evaporated by a rotary evaporator to obtain a solid product; the solid product was placed in a drying oven at a temperature of 130°C and dried for 4h. Then, it was calcined in a muffle furnace at a temperature of 550°C for 6h to obtain an isobutane dehydrogenation to isobutylene catalyst Cat-2, in which the isobutane dehydrogenation to isobutylene catalyst Cat-2, based on the total weight of the isobutane dehydrogenation to isobutylene catalyst Cat-2, the content of the platinum component in terms of platinum element is 0.4% by weight, the content of the tin component in terms of tin element is 1.2% by weight, and the rest is a carrier.
[0102] Example 3
[0103] This example is used to illustrate the preparation of the olite mesoporous composite material, the preparation method of the isobutane dehydrogenation catalyst to prepare isobutane, and its application in the isobutane dehydrogenation reaction.
[0104] (1) Preparation of mesoporous composite materials of enamel
[0105] 1.0 g of triblock copolymer polyethylene glycol-polypropylene glycol-polyethylene glycol (Aldrich, P123) and 1.69 g of ethanol were added to 28 ml of acetic acid and sodium acetate buffer solution (pH = 4.4), and stirred at 15°C until the polyethylene glycol-polypropylene glycol-polyethylene glycol was completely dissolved, then 6 g of trimethylpentane was added to the above solution, and stirred at 15°C for 8 hours, and then 2.13 g of tetramethoxysilane was added to the above solution, and stirred at 15°C for 20 hours, and then the solution was transferred to a polytetrafluoroethylene-lined reactor, and after oven crystallization at 60°C for 24 hours, it was filtered and washed with distilled water to obtain a mesoporous material filter cake;
[0106] A 15 wt % water glass and a 12 wt % sulfuric acid solution were reacted for 1.5 hours at a water glass: sulfuric acid weight ratio of 5:1, the pH was adjusted to 3 with 98 wt % sulfuric acid, and the reaction material was filtered and washed with distilled water until the sodium ion content was 0.02 wt %, to obtain a silica gel filter cake.
[0107] Put 1 gram of mesoporous silica filter cake, 10 grams of silica gel filter cake and 10 grams of diatomite powder prepared above into a 100 ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3 mm, the number is 1, and the rotation speed is 400 r / min. Close the ball mill, and mill at 60°C for 1 hour to obtain 18 grams of solid powder; dissolve the solid powder in 30 grams of deionized water, spray dry at 200°C and 12000 r / min; calcine the product obtained after spray drying at 500°C in a muffle furnace for 8 hours to remove the template agent, and obtain 15 grams of the target product of the template agent removal. One-dimensional pore double pore distribution diatomite mesoporous composite material carrier diatomite mesoporous composite material A3 has a specific surface area of 100m 2 / g, the pore volume is 1.0ml / g, and the average pore diameter is 8nm and 20nm.
[0108] X-ray diffraction characterization shows that the iodite mesoporous composite material A3 has a 2D hexagonal pore structure.
[0109] (2) Preparation of catalyst for dehydrogenation of isobutane to isobutene
[0110] 0.107g H2PtCl6·6H2O and 0.294g ZnCl2 were dissolved in 100mL deionized water in a round-bottom flask to obtain a mixed solution; 10g of the modified olite mesoporous composite material A3 prepared above was added to the mixed solution for co-impregnation treatment, and the reaction was continuously stirred for 20 hours in a water bath at 20°C, and the solvent water in the system was evaporated by a rotary evaporator to obtain a solid product; the solid product was placed in a drying oven at a temperature of 70°C and dried for 16h. Then, the isobutane dehydrogenation isobutylene catalyst Cat-3 was obtained, in which the total weight of the isobutane dehydrogenation isobutylene catalyst Cat-3 was used as the basis, the content of the platinum component in terms of platinum element was 0.4% by weight, the content of the zinc component in terms of zinc element was 1.4% by weight, and the rest was the carrier.
[0111] Example 4
[0112] This example is used to illustrate the preparation of the olite mesoporous composite material, the preparation method of the isobutane dehydrogenation catalyst to prepare isobutane, and its application in the isobutane dehydrogenation reaction.
[0113] (1) Preparation of mesoporous composite materials of enamel
[0114] 1.0 g of triblock copolymer polyethylene glycol-polypropylene glycol-polyethylene glycol (Aldrich, P123) and 1.69 g of ethanol were added to 28 ml of acetic acid and sodium acetate buffer solution (pH = 4.4), and stirred at 15°C until the polyethylene glycol-polypropylene glycol-polyethylene glycol was completely dissolved, then 6 g of trimethylpentane was added to the above solution, and stirred at 15°C for 8 hours, and then 2.13 g of tetramethoxysilane was added to the above solution, and stirred at 15°C for 20 hours, and then the solution was transferred to a polytetrafluoroethylene-lined reactor, and after oven crystallization at 60°C for 24 hours, it was filtered and washed with distilled water to obtain a mesoporous material filter cake;
[0115] A 15 wt % water glass and a 12 wt % sulfuric acid solution were reacted for 1.5 hours at a water glass: sulfuric acid weight ratio of 5:1, the pH was adjusted to 3 with 98 wt % sulfuric acid, and the reaction material was filtered and washed with distilled water until the sodium ion content was 0.02 wt %, to obtain a silica gel filter cake.
[0116] Put 1 gram of mesoporous silica filter cake, 1 gram of silica gel filter cake and 10 grams of diatomite powder prepared above into a 100 ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3 mm, the number is 1, and the rotation speed is 400 r / min. Close the ball mill, and mill at 60°C for 1 hour to obtain 10 grams of solid powder; dissolve the solid powder in 30 grams of deionized water, spray dry at 200°C and 12000 r / min; calcine the product obtained after spray drying at 500°C in a muffle furnace for 8 hours to remove the template agent, and obtain 8 grams of the target product with one-dimensional pore double pore distribution diatomite mesoporous composite material carrier diatomite mesoporous composite material A4 has a specific surface area of 50m 2 / g, the pore volume is 1.0ml / g, and the average pore diameter is 7nm and 20nm.
[0117] (2) Preparation of catalyst for dehydrogenation of isobutane to isobutene
[0118] 0.053 g H2PtCl6·6H2O, 0.118 g SnCl4·5H2O and 0.412 g Zn(NO3)2·6H2O were dissolved in 100 mL deionized water in a round-bottom flask to obtain a mixed solution; 10 g of the modified iodite mesoporous composite material A4 prepared above was added to the mixed solution for co-impregnation treatment, and after continuous stirring and reaction for 2 hours in a water bath at 100° C., the solvent water in the system was evaporated by a rotary evaporator to obtain a solid product; the solid product was placed in a drying oven at a temperature of 150° C. and dried for 3 hours. Then, the catalyst is calcined in a muffle furnace at a temperature of 650° C. for 3 h to obtain an isobutane dehydrogenation to isobutene catalyst Cat-4. In the isobutane dehydrogenation to isobutene catalyst Cat-4, based on the total weight of the isobutane dehydrogenation to isobutene catalyst Cat-4, the content of the platinum component calculated as platinum element is 0.2 weight%, the content of the tin component calculated as tin element is 0.4 weight%, the content of the zinc component calculated as zinc element is 0.8 weight%, and the rest is a carrier.
[0119] Comparative Example 1
[0120] This example is used to illustrate a reference method for preparing a catalyst for isobutane dehydrogenation to isobutane and its application in an isobutane dehydrogenation reaction.
[0121] The isobutane dehydrogenation to isobutylene catalyst Cat-D-1 was prepared according to the method of Example 1, except that: the isobutane dehydrogenation to isobutylene catalyst was prepared by directly using unactivated olite powder as a carrier to load the metal component, and the catalyst preparation process was the same as that of Example 1. Based on the total weight of the catalyst Cat-D-1, the content of the platinum component in terms of platinum element was 0.5% by weight, the content of the tin component in terms of tin element was 0.7% by weight, the content of the zinc component in terms of zinc element was 0.8% by weight, and the rest was the carrier.
[0122] Comparative Example 2
[0123] This example is used to illustrate the preparation of a reference isobutane dehydrogenation catalyst to produce isobutane and its application in the isobutane dehydrogenation reaction.
[0124] The isobutane dehydrogenation to isobutylene catalyst Cat-D-2 was prepared according to the method of Example 1, except that the ball milling process was cancelled, and 1 gram of mesoporous silica filter cake, 1 gram of silica gel filter cake and 10 grams of diatomite powder were directly dissolved in 30 grams of deionized water for pulping, spray drying and high-temperature calcination were performed to obtain a modified diatomite mesoporous composite material D2, and the diatomite mesoporous composite material D2 was used as a carrier to load the metal component to prepare the isobutane dehydrogenation to isobutylene catalyst, and the catalyst preparation process was the same as that of Example 1. Based on the total weight of the catalyst Cat-D-2, the content of the platinum component in terms of platinum element was 0.3% by weight, the content of the tin component in terms of tin element was 0.6% by weight, the content of the zinc component in terms of zinc element was 0.7% by weight, and the rest was the carrier.
[0125] Comparative Example 3
[0126] This example is used to illustrate a reference method for preparing a catalyst for isobutane dehydrogenation to isobutane and its application in an isobutane dehydrogenation reaction.
[0127] The isobutane dehydrogenation to isobutylene catalyst Cat-D-3 was prepared according to the method of Example 1, except that the high-temperature calcination process was cancelled, and 10 grams of mesoporous silica filter cake, 10 grams of silica gel filter cake and 10 grams of diatomite powder were subjected to ball milling and spray drying, but no high-temperature calcination was performed to remove the template agent, thereby obtaining a modified diatomite mesoporous composite material D3, and the modified diatomite mesoporous composite material D3 was used as a carrier to load the metal component to prepare an isobutane dehydrogenation to isobutylene catalyst, and the catalyst preparation process was the same as step (3) in Example 1. Based on the total weight of the catalyst Cat-D-3, the content of the platinum component in terms of platinum element was 0.3% by weight, the content of the tin component in terms of tin element was 0.6% by weight, the content of the zinc component in terms of zinc element was 0.7% by weight, and the rest was the carrier.
[0128] Comparative Example 4
[0129] This example is used to illustrate a reference method for preparing a catalyst for isobutane dehydrogenation to isobutane and its application in an isobutane dehydrogenation reaction.
[0130] The isobutane dehydrogenation to isobutylene catalyst Cat-D-4 was prepared according to the method of Example 1, except that: "calcined at 500°C in a muffle furnace for 8 hours" was changed to "calcined at 500°C in a muffle furnace for 10 hours", to obtain a modified high specific surface mesoporous material D4, and the modified high specific surface mesoporous material D4 was used as a carrier to load the metal component to prepare the isobutane dehydrogenation to isobutylene catalyst, and the catalyst preparation process was the same as in Example 1. Based on the total weight of the catalyst Cat-D-4, the content of the platinum component in terms of platinum element was 0.3% by weight, the content of the tin component in terms of tin element was 0.6% by weight, the content of the zinc component in terms of zinc element was 0.7% by weight, and the rest was the carrier.
[0131] Comparative Example 5
[0132] The invention is used to illustrate the preparation method of a reference isobutane dehydrogenation catalyst to produce isobutane and its application in isobutane dehydrogenation reaction.
[0133] The isobutane dehydrogenation to isobutene catalyst Cat-D-5 was prepared according to the method of Example 2. The difference is that the process is as follows:
[0134] The mesoporous composite material A2 of the gypsum stone was placed in a muffle furnace, the nitrogen protection was cancelled, and the first calcination treatment was carried out. At a heating rate of 4°C / min, the temperature was raised from 30°C to 400°C and maintained at 400°C for 8h. After the first calcination treatment, the heating was stopped, and the sample temperature was cooled to room temperature in the air before the second calcination treatment. During the second calcination treatment, the temperature was raised from 25°C to 500°C at a heating rate of 6°C / min and maintained at 500°C for 10h. After the second calcination treatment, the sample was cooled to room temperature in the air. Take 10g of the above sample and put it into a 100ml ball milling jar, and ball milling was carried out under nitrogen protection to obtain 10g of modified gypsum stone mesoporous composite material D4 with an average particle diameter of 12μm. Among them, the material of the ball milling jar is polytetrafluoroethylene, the material of the grinding ball is agate, the diameter of the grinding ball is 6mm, the number of grinding balls is 40, the grinding ball speed is 100r / min, the temperature in the ball milling jar is 10°C, and the ball milling time is 15 hours.
[0135] The modified mesoporous material D4 was used as a carrier to load the metal component to prepare a catalyst for isobutane dehydrogenation to isobutene, and the catalyst preparation process was the same as in Example 2. Based on the total weight of the catalyst Cat-D-5, the content of the platinum component in terms of platinum element was 0.4 weight percent, the content of the tin component in terms of tin element was 1.2 weight percent, and the rest was the carrier.
[0136] Test Example 1
[0137] Testing of the performance of isobutane dehydrogenation to isobutene catalyst in isobutane dehydrogenation reaction.
[0138] 0.5 g of the isobutane dehydrogenation catalyst prepared in the above embodiment and comparative example was respectively loaded into a fixed bed quartz reactor, and the reaction temperature was controlled to be 590° C., the reaction pressure was 0.1 MPa, the molar ratio of isobutane to hydrogen was 1:1, the reaction time was 50 h, and the mass space velocity of isobutane was 4 h -1 The reaction product separated by the Al2O3-S molecular sieve column directly enters the Agilent 7890A gas chromatograph equipped with a hydrogen flame detector (FID) for online analysis to obtain the isobutane conversion rate and isobutene selectivity. The test results are shown in Table 1, which shows the performance of the isobutane dehydrogenation to isobutene catalyst obtained in the examples of the present invention and the comparative examples in the isobutane dehydrogenation reaction.
[0139] Table 1
[0140]
[0141]
[0142] As can be seen from Table 1, the dehydrogenation catalyst prepared by the method of the present invention has excellent performance when used for the isobutane dehydrogenation to isobutene reaction. By comparing the experimental results of catalyst Cat-1 and catalysts Cat-D-1, Cat-D-2, Cat-D-3, Cat-D-4, and Cat-D-5, it can be found that the iodite mesoporous composite material that has been calcined at high temperature and ball-milled once is more suitable as a carrier for the isobutane dehydrogenation reaction catalyst, and can effectively improve the isobutane conversion rate and isobutene selectivity.
[0143] Obviously, the material ratio of the diatomite mesoporous composite material provided by the present invention can effectively improve the pore structure of the mesoporous material, including improving the specific surface area, pore volume and average pore size of the material. With the modified diatomite mesoporous composite material as a carrier, the metal component is loaded to obtain an isobutane dehydrogenation to isobutylene catalyst. When the catalyst is used for the isobutane dehydrogenation reaction, the catalytic effect of both the isobutane conversion rate and the isobutylene selectivity can be obtained when the metal component loading is low.
[0144] In addition, the isobutane dehydrogenation to isobutene catalyst prepared by the method of the present invention does not use activated alumina as a carrier, thus overcoming the problem that the catalyst surface currently prepared by using activated alumina carriers is prone to carbon deposition, which leads to rapid deactivation.
[0145] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a spherical glazeite mesoporous composite material, characterized in that: The preparation method comprises: (1) in the presence of a template, trimethylpentane and ethanol, tetramethoxysilane is brought into contact with an acidic aqueous solution for the first time to obtain a mixture, and the mixture is subjected to crystallization, suction filtration and washing to obtain a mesoporous silica filter cake; (2) contacting the water glass with the inorganic acid for a second time, and filtering and washing the mixture obtained after the second contact to obtain a silica gel filter cake; (3) ball-milling the mesoporous silica filter cake, the silica gel filter cake and the elutingite together to obtain a solid powder; (4) preparing the solid powder into a slurry in the presence of deionized water and then spray drying the slurry; (5) calcining the product obtained in step (4) to remove the template, thereby obtaining a spherical izolite mesoporous composite material.
2. The preparation method according to claim 1, wherein In step (1), the template is a triblock copolymer of polyethylene oxide-polyoxyisobutylene-polyoxyethylene; And / or, the acidic aqueous solution is a buffer solution of acetic acid and sodium acetate, and the pH value of the buffer solution is 1-6; And / or, the temperature of the first contact is 10-60° C., and the contact time is 10-72 hours; And / or, the crystallization temperature is 30-150° C., and the crystallization time is 10-72 hours.
3. The preparation method according to claim 1, wherein In step (2), the pH value of the solution of water glass and the inorganic acid is 2-4; And / or, the temperature of the second contact is 10-60° C., and the contact time is 1-5 hours.
4. The preparation method according to claim 1, wherein In step (2), the molar ratio of the template: the ethanol: the acidic aqueous solution: the trimethylpentane: the tetramethoxysilane is 1: (100-500): (150-900): (200-500): (50-200); And / or, the weight ratio of the water glass to the inorganic acid is (3-6):1; And / or, the weight ratio of the mesoporous silica filter cake, the silica gel filter cake and the ellipse is (1-10):(1-10):(1-10).
5. A spherical iodite mesoporous composite material prepared by the preparation method according to any one of claims 1 to 4.
6. The spherical iodite mesoporous composite material according to claim 5, wherein: The spherical eidolite mesoporous composite material has an average particle diameter of 20-60 microns, a specific surface area of 50-600 square meters / gram, a pore volume of 0.5-1.5 milliliters / gram, and a most probable pore diameter of 2-15 and 10-40 nanometers.
7. A catalyst for dehydrogenating isobutane to isobutene, characterized in that: The isobutane dehydrogenation catalyst for producing isobutene comprises a carrier and an active metal component supported on the carrier, wherein the carrier is the spherical iodite mesoporous composite material according to claim 5 or 6.
8. The catalyst for preparing isobutylene by dehydrogenation of isobutane according to claim 7, wherein: The active metal component is selected from one or more of platinum, tin, zinc, magnesium, calcium and gallium; preferably one or more of platinum, tin and zinc; more preferably contains platinum and contains tin and / or zinc.
9. The catalyst for preparing isobutylene by dehydrogenation of isobutane according to claim 8, wherein: Based on the total weight of the isobutane dehydrogenation catalyst for preparing isobutene, the content of the modified olite mesoporous composite material is 98-99 weight %, the content of the active component Pt calculated as Pt element is 0.2-0.5 weight %, and the content of other active metal components other than Pt calculated as metal elements is 0.8-1.5 weight %; Preferably, based on the total weight of the isobutane dehydrogenation to isobutene catalyst, the content of the eidolite mesoporous composite material is 98.0-99.0 weight %, the content of the main active component Pt calculated as Pt element is 0.2-0.5 weight %, the content of Sn calculated as Sn element is 0.4-0.7 weight %, and the content of Zn calculated as Zn element is 0.4-0.8 weight %.
10. Use of the catalyst for preparing isobutylene by dehydrogenation of isobutane according to any one of claims 7 to 9 in the dehydrogenation reaction of isobutane; Preferably, the conditions for the isobutane dehydrogenation reaction include: The reaction temperature is 530-630℃, the reaction pressure is 0.05-0.3MPa, the molar ratio of isobutane to hydrogen in the raw material is 1:(0.2-5), and the mass space velocity of isobutane is 1h -1 -10h -1 .
Citation Information
Patent Citations
Isobutane dehydrogenation catalyst using spherical double-mesoporous zeolite composite material as carrier, preparation method and applications thereof
CN110732340A
Organometallic framework material, preparation and use
CN1910191A
Reactor with one or more fluid supply lines and flow distribution device for said fluid streams
EP2703076A1
Dehydrogenation of hydrocarbons with a multimetallic catalytic composite
US3998900A
Bimetallic catalysts for dehydroisomerization of N-butane to isobutene
US5198597A